Pengembangan Media Pembelajaran Leap Motion Materi Pengenalan Hewan untuk Meningkatkan Motorik Anak Usia Dini - Esti Kurniawati Mahardika; Gunawan Wiradharma; Mario Aditya Prasetyo; Khaerul Anam; Muktia Pramitasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop an interactive learning medium based on Leap Motion, namely LeapZoo: Zoo-Based Educational Game, which is designed to improve early childhood motor skills through virtual animal recognition. The method used was research and development (R&D) with the ADDIE model, focusing on the design and development stages. Validation was carried out by media, language, and early childhood education experts to assess technical and pedagogical feasibility. The results showed that LeapZoo is feasible to be used as a learning medium in early childhood education. In conclusion, gesture-based interactions such as stroking and feeding animals can stimulate children’s fine and gross motor coordination and align with Vygotsky’s theory, which emphasizes the role of social interaction and digital scaffolding in the zone of proximal development. Keywords: Early Childhood, Gesture-Based Learning, Leap Motion, Learning Media, Motor Skills, Animal Recognition